1999
DOI: 10.1038/sj.bjp.0702905
|View full text |Cite
|
Sign up to set email alerts
|

Efficient functional coupling of the human D3 dopamine receptor to Go subtype of G proteins in SH‐SY5Y cells

Abstract: a human neuroblastoma cell line, SH-SY5Y, produced much greater signals than those expressed in a human embryonic kidney cell line, HEK293. Quinpirole, a prototypic agonist, markedly inhibited forskolin-stimulated cyclic AMP production and Ca 2+ -channel (N-type) currents in SH-SY5Y cells, and enhanced GTPg 35 S binding in isolated membranes, nearly ten times greater than that observed in HEK293 cell membranes. 3 GTPg 35 S-bound Ga subunits from quinpirole-activated and solubilized membranes were monitored upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…It is possible that in these mice, the effects that remained after administering doses of 10 nmol morphine and above are produced by the activity of Gai/o subunits on effectors other than those acted upon by the Gaz subunits. Indeed, there are some reports detailing the preferences of different classes of G proteins in the regulation of certain effectors, for example, Gao and adenylyl cyclase V (Zaworski et al, 1999), Gaz, and adenylyl cyclases II and VI (Ho et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that in these mice, the effects that remained after administering doses of 10 nmol morphine and above are produced by the activity of Gai/o subunits on effectors other than those acted upon by the Gaz subunits. Indeed, there are some reports detailing the preferences of different classes of G proteins in the regulation of certain effectors, for example, Gao and adenylyl cyclase V (Zaworski et al, 1999), Gaz, and adenylyl cyclases II and VI (Ho et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of assay, an immunoprecipitation step was incorporated using antisera raised against the C-terminal decapeptide of G␣ i1/2 (i and ii), G␣ i3 (iii), or G␣ o1 (iv). The significance of differences between basal and dopaminestimulated [ to G␣ o1 (Zaworski et al, 1999;Beom et al, 2004), although Zaworski et al postulated that efficient coupling to G␣ o1 required the expression of adenyl cyclase subtype V. However, this study is the first to assess coupling to each of the four G␣ i/o subunits directly and, in parallel, to explore pharmacological consequences of attempting to expand the G protein coupling profile of the D 3 receptor. Key to this process was maintaining a clearly defined receptor to G protein expression stoichiometry, and, despite using both a series of transient cotransfection studies and establishing cells lines stably expressing dopamine receptors that allowed regulated expression of a G protein, this was only possible by using GPCR-G protein fusion proteins.…”
Section: S]gtp␥s Binding (Open Bars) and The Effect Of 10mentioning
confidence: 99%
“…Initial reports indicated that the D 3 receptor, when expressed in a variety of cell systems, did not exhibit a decrease in affinity for agonists in the presence of guanine nucleotides and did not modulate adenylate cyclase activity (Sokoloff et al, 1990;Freedman et al, 1994;Tang et al, 1994). However, more recently, it has been shown that dopaminergic agonists dose-dependently stimulate guanosine 5Ј-O-(thiotriphosphate) ([ 35 S]GTP␥S) binding in Sf-9 insect cells (Alberts et al, 2000), Chinese hamster ovary cells (Malmberg et al, 1998;Newman-Tancredi et al, 1999;Vanhauwe et al, 1999;Vanhauwe et al, 2000), and SH-SY5Y human neuroblastoma cells (Zaworski et al, 1999) in which the D 3 receptor was expressed. Because these effects were abolished by pertussis toxin treatment, they must reflect activation of one, or more, members of the "G i " G protein family.…”
mentioning
confidence: 99%
“…There are a number of phenotypic drug responses associated with cell types that are not specifically ascribed to mechanisms but are nevertheless noted in the literature (i.e., levomedetomidine for ␣ 2A -adrenoceptors (Jansson et al, 1998;Kukkonen et al, 2001), isoprostane 8-iso-prostaglandin F for thromboxane A 2 receptors (Weber and Markillie, 2003), and quinpirole for dopamine D 3 and D 2 receptors (Zaworski et al, 1999;Alberts et al, 2000). In addition, cells can adjust their signaling capability according to their needs through control of reagents required for receptor phosphorylation [i.e., through GRKs (Lohse, 1993;Zamah et al, 2002;Ribas et al, 2007;Tobin et al, 2008) or protein kinase A (Daaka et al, 1997;Tobin, 2008)] and internalization.…”
Section: Tm Receptors As Shapeshifting Proteinsmentioning
confidence: 99%